The relative anthelmintic efficacy of plant-derived cysteine proteinases on intestinal nematodes. Issue 2 (31st October 2013) - Luoga, W.; Mansur, F.; Buttle, D.J.; Duce, I.R.; Garnett, M.C.; Lowe, A.; Behnke, J.M.
Abstract: We examined the in vitro and in vivo efficacy of plant cysteine proteinases (CPs) derived from pineapple ( Ananas comosus ) and kiwi fruit ( Actinidia deliciosa ), and compared their efficacy as anthelmintics to the known effects of CPs from the latex of papaya ( Carica papaya ) against the rodent intestinal nematode, Heligmosomoides bakeri. Both fruit bromelain and stem bromelain had significant in vitro detrimental effects on H. bakeri but in comparison, actinidain from kiwi fruit had very little effect. However, in vivo trials indicated far less efficacy of stem bromelain and fruit bromelain than that expected from the in vitro experiments (24.5% and 22.4% reduction in worm burdens, respectively) against H. bakeri. Scanning electron microscopy revealed signs of cuticular damage on worms incubated in fruit bromelain, stem bromelain and actinidain, but this was far less extensive than on those incubated in papaya latex supernatant. We conclude that, on the basis of presently available data, CPs derived from pineapples and kiwi fruits are not suitable for development as novel anthelmintics for intestinal nematode infections.